Effects of a Sensorimotor Training Program on Static Equilibrium in Swimmers with Down Syndrome and Intellectual Disability - Hernández Chacón, Milena (2023)
Purpose: This study seeks to determine the effect of a sensorimotor training program on static equilibrium in swimmers with Down syndrome and intellectual disability. Method: Participants: a total of 13 swimmers. Instruments and materials: the Modified Clinical Test for Sensory Integration for Balance, a Wii device with a platform, and a computer with a program to analyze the center of gravity were used in the study. Procedures: a pretest was applied, then a neuromotor training was delivered for four weeks, in three sessions of 30 minutes each, and finally, a posttest was applied. Since they were active athletes, they continued their routine without altering the training load. Statistical analysis: descriptive statistics and a two-way ANOVA (2x2, measures and groups) were used. Results: there were no statistically significant differences between the variables measured (F = 0.14, p = 0.7162) or per groups (F = 0.2, p = 0.6659) for the variable open eyes on a stable surface. For the variable closed eyes on an unstable surface, there were significant differences between the variables measured (F = 0.952, p = 0.350) and between groups (F = 6.066, p = 0.320), while for open eyes on an unstable surface there were no differences between the variables measured (F = 0.852, p = 0.376) or between groups (F = 2, .484, p = 0.143). For the variable closed eyes on a stable surface there were no significant differences between the variables measured (F = 0.716, p = 0.415) or between groups (F = 0.801, p = 0.390). It was found that this training in this population produced an improvement (p <0.05) for the variable closed eyes on a stable surface 0.32.